Bridging Photonics and Optoelectronics Curriculum for the Solar Photovoltaic and LED Industries - Yu-Shan Su; Han-Chao Chang (International Journal of Photoenergy)
The gap between learning courses and practical demands has existed in Taiwanese solar photovoltaic and LED industries; therefore, this study attempts to analyze the existing curriculum design of universities. This study collected the current 103 course programs from all optoelectronics-related departments in Taiwanese 36 colleges and universities and sorted these curriculums by three domains of education objectives theory. This theoretical framework was verified on the basis of samples from 150 Taiwanese industrial experts and 354 optoelectronics-related undergraduates and postgraduates. We found that the levels of correlation among the independent variables including cognitive, affective, and skill-based domains and the dependent variable employability are all positively related to each other. We also found the currently curriculum design in Taiwanese universities rarely fit into theory of education objectives from the results of multiple regression analysis. Industrial and student’s group also have few consistent ideas on courses within the curriculum. Finally in order to bridge the gap between learning and practical application, the study provides an idea on curriculum design and suggests that curriculum review should be executed by industrial experts to confirm the courses related to the employability.